2021
DOI: 10.3390/ma14102532
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on the Physical and Rheological Properties of Trinidad Lake Asphalt Modified Bitumen

Abstract: The application of various modifiers has emerged in recent years to improve conventional petroleum-based bitumen properties. The natural asphalt called Trinidad Lake Asphalt (TLA) has been applied very often due to its consistent properties, high viscosity and density, and superior rheological properties, and effective blending with other bitumen. However, most studies on TLA-modified binders always focused on physical and rheological properties in the original (unaged) condition, but the details about aging p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The additional results of a comprehensive laboratory investigation on the physical and rheological properties of the 35/50 base bitumen modified by the addition of three different TLA contents (0, 10, and 20% by weight) as well as on the effect of short-term ageing on these physical and rheological characteristics were presented by the authors elsewhere [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional results of a comprehensive laboratory investigation on the physical and rheological properties of the 35/50 base bitumen modified by the addition of three different TLA contents (0, 10, and 20% by weight) as well as on the effect of short-term ageing on these physical and rheological characteristics were presented by the authors elsewhere [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The result of fitting ZSV to the static indentation is about 95%, the slightly worse relationship can be observed using the regression results for the dynamic indentation (90%). It is worth emphasizing that the authors carried out similar estimations for other test conditions: the TLA-modified binders in the original (unaged) state, creep test of ZSV instead of oscillatory test and three temperatures of ZSV test in the range of 40–60 °C [ 55 , 56 ]. The analysis revealed that not one of these considered test conditions had a significant influence on the static as well as dynamic indentation test results.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, TLA contains about 54% bitumen, 36% minerals and 10% other useful substances. The minerals are very small, 90% of the minerals have a particle size of less than 0.075 mm [22], and the aged bitumen in RAP is also relatively hard, both of which can improve the softening point and wear resistance of the asphalt. Finally, both RAP and TLA can increase the thickness of the asphalt mold and increase the friction coefficient of the road surface.…”
Section: Xrf Analysismentioning
confidence: 99%
“…Studies conducted by Li [ 11 ] and Cao et al [ 12 ] demonstrate the impact of RTFOT, PAV, and UV aging tests on the fundamental properties of asphalt. Several researchers argue that analyzing the high-temperature performance of asphalt through its rheological properties is more scientifically rigorous [ 13 , 14 ]. The dynamic shear rheological (DSR) test is utilized to investigate the high-temperature rheological properties of asphalt, while the rutting factor (G*/sinδ) serves as an indicator for evaluating its high-temperature performance [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%